Export-import financing : a practical guide - Schneider, Gerhard W. (New York : Ronald Press Co., 1974)
The financing of trade requires enormous amounts of capital in the form of various types of loans and advances, as well as other financial services as guarantees and letters of credit.
Includes index
includes bibliographical references
II 17/01/2019
Loans
Keywords: Export credit; Negotiable instruments; Foreign trade promotion; Exports; Imports